Unveiling the Aggregation Behavior of Doxorubicin Hydrochloride in Aqueous Solution of 1-Octyl-3-methylimidazolium Chloride and the Effect of Bile Salt on These Aggregates A Microscopic Study - Pyne, Arghajit (Langmuir : the ACS journal of surfaces and colloids, 2018)
In this article, we have unveiled the aggregation behavior of a potent chemotherapeutic drug, doxorubicin hydrochloride (Dox) in a well-known imidazolium based surface active ionic liquid (SAIL), 1-octyl-3-methylimidazolium chloride (C8mimCl). The aggregates formed by Dox in C8mimCl have been characterized using dynamic light scattering (DLS), fluorescence lifetime imaging microscopy (FLIM), high-resolution transmission electron microscopy (HR-TEM), analytical transmission electron microscopy (analytical TEM), field emission scanning electron microscopy (FESEM), atomic force microscopy (AFM), and Fourier-transform infrared spectroscopy (FTIR) measurements. It is found that Dox forms large spherical aggregates in the presence of C8mimCl SAIL. We have also explored the driving force behind this aggregation behavior of Dox in C8mimCl. Furthermore, it is observed that in the presence of a common bile salt, sodium cholate (NaCh), Dox/C8mimCl spherical aggregates disrupt to form rodlike fibrillar aggregates. Therefore, formation of spherical aggregates and also its disruption into rodlike fibrillar aggregates have been performed, and this is expected to open a new scope for the design of a new generation smart drug delivery system where the drug itself aggregates to form the delivery system